Monophonic and m-hull number of the cartesian product of graphs - Paluga, Esamel M. (Utilitas Mathematica, 2009)
In this paper, we use the concept of block graph to characterize the monophonic sets in G × Kn, where G is a graph containing a cutpoint and Kn is the complete graph of order n. We also give the monophonic and m-hull numbers of graphs resulting from the cartesian product of two graphs.